The industrial electronics handbook - Wilamowski, Bogdan M.; Irwin, J. David, 1939- (Electrical engineering handbook series., 2011)
Fundamentals of Industrial Electronics is the first volume in The Industrial Electronics Handbook, Second Edition. It focuses on the fundamental areas which form the basis for the field of industrial electronics. Because of the breadth of this field, the knowledge required spans a wide spectrum of technology that includes analog and digital circuits, electronics, electromagnetics, machines, and signal processing. The four other volumes in the Handbook are also available individually: Industrial Communication Systems, Intelligent Systems, Power Electronics and Motor Drives, and Control and Mecha.